Nevoid basal cell carcinoma syndrome (Gorlin syndrome): a case report - Noura Abdul Rahman; Fatima Breim; Joud Zakour; Zainab Srouji; Silva Ishkhanian (Journal of Medical Case Reports, 2025)
Abstract Background Basal cell nevus syndrome, also known as Gorlin or Gorlin–Goltz syndrome, is a hereditary condition caused by mutation in the PATCHED gene. The syndrome presents with a wide range of clinical manifestations, including basal cell carcinomas, jaw cysts, and skeletal anomalies. Diagnosis is based on specific criteria, and treatment typically includes surgical removal of basal cell carcinomas. Case presentation A 36-year-old Middle Eastern man presented with multiple pigmented ulcerated lesions on his face, scalp, and trunk, consistent with basal cell carcinomas. A history of a previous jaw cyst excision and characteristic physical examination findings led to the diagnosis of Gorlin–Goltz syndrome. Treatment included surgical excision of high-risk lesions and intralesional 5-fluorouracil injections for superficial lesions. The patient showed positive responses to the treatment, with most lesions healing completely and others showing ongoing improvement. Minimal side effects were observed, highlighting the potential efficacy of this novel approach in managing basal cell carcinomas associated with Gorlin–Goltz syndrome. Conclusion Gorlin syndrome is a rare genetic disorder characterized by various clinical manifestations, with basal cell carcinomas being a prominent feature. Diagnosis is based on specific major and minor criteria, and a multidisciplinary approach is crucial for effective management. Basal cell carcinomas in Gorlin syndrome tend to occur more commonly in sun-exposed areas, necessitating sun protection. Treatment options include surgical excision, cryotherapy, photodynamic therapy, and topical chemotherapeutics, based on lesions characteristics. This case report describes a novel approach to treating multiple basal cell carcinomas associated with basal cell nevus syndrome using intralesional 5-fluorouracil injections. The observed side effects were minimal, demonstrating the potential efficacy of this treatment modality.